Application of low-cost hydrokinetic technology for accelerating electricity access to rural areas in developing economies: field experiment in Kenya - Willis Awandu; Jens-Uwe Wiesemann; Boris Lehmann (Environmental Research Communications)
This article presents the design, construction and field test of an experimental prototype of a low-cost hydrokinetic turbine technology made of local materials and e-waste components. The aim of this study is to investigate the performance of the turbine when subjected to field conditions in low flow velocity rivers. The research and development (R&D) involve the use of e-waste boat motor and locally available materials to develop a modular hydrokinetic turbine for generation of electricity using kinetic energy of rivers. A decommissioned boat motor with a 0.24 m diameter rotor is operated as a turbine. A shroud for flow acceleration was developed from 1.5 mm thick stainless-steel plates and a support structure constructed using angle lines. The field test results of the prototype generated about 11.543 ± 0.021 W and 37.129 ± 0.021 W or (equivalent of 0.011543 kWh and 0.037129 kWh) when operated at an approach flow velocity of 0.8 m s ^−1 and 1.2 m s ^−1 respectively. The wire to water ratio was determined instead of the C _p and the turbine achieved an overall wire to water efficiency of 0.99 and 0.95 respectively. This prototype technology can sustainably provide 24 h energy, sufficient to charge batteries in the rural areas and also provide opportunities within the community such as mobile charging points. An upscaled version of this low-cost technology can be adaptable in rural off-grid communities to enhance the access to electricity in developing countries.